Personal Meaning in the Lives of a Shoplifting Population - McShane, Frank J. (International journal of offender therapy and comparative criminology, 1991)
The purpose of this study was twofold. First, the study evaluated the effectiveness of personal meaning as measured by the Purpose in Life (PIL) and Seeking of Noetic Goals (SONG) tests in discriminating shoplifters from nonshoplifters. The second objective was to provide a more systemic examination of the relationship between several demographic, psychosocial stressor and attitudinal variables, and the act of shoplifting. Data were collected from 75 persons immediately after they had been apprehended for shoplifting and compared with data obtained from 75 undergraduate student nonshoplifters. Results of discriminant analysis indicate that there are meaningful differences between shoplifters and nonshoplifters, and provide support for the continued use of the SONG as an important supplemental to the PIL with clinical populations. Implications are discussed